Future Scenarios of the Lithuanian School: “What’s the Point?“ - Duoblienė, Lilija; Kontrimienė, Simona; Vaitekaitis, Jogaila; Garbauskaitė-Jakimovska, Justina; Kairė, Sandra (Acta Paedagogica Vilnensia, 2023)
The article presents the results of our research project and development of four futuristic scenarios for the Lithuanian school attempting to answer the question: What’s the point? The idea of the article matured during the ongoing presentations of the project insights in public academic space, where two questions were often posed: What’s the point of this? What are the practical benefits? Therefore, the article features the methodology of scenario development and describes the benefits of these and similar scenarios, why they are created, and the possible benefits of the scenarios developed within the framework of this project.
Keywords: Lithuania; school; scenarios; Delphi research method